Let $a$, $b$ and $c$ be non-negative numbers such that $a^4+b^4+c^4=3$. Prove that: $$\frac{1}{3-2ab}+\frac{1}{3-2ac}+\frac{1}{3-2bc}\leq3$$ I tried SOS, C-S and more, but without success.

By brute force methods with computer we can get that this inequality is true, but I am looking for an human proof, which we can release during a competition.

Thank you!

  • $\begingroup$ Oh, I see the problem now. $\endgroup$ – Sangchul Lee Dec 25 '16 at 4:28
  • $\begingroup$ @Sangchul Lee Thank you for your interest! $\endgroup$ – Michael Rozenberg Dec 25 '16 at 4:31
  • $\begingroup$ I have a partial proof of this do you want to see that ? Moreover it's short and clear .Perhaps this could inspire you... :) $\endgroup$ – user448747 Aug 14 '17 at 16:13
  • $\begingroup$ @FatsWallers I think it's better to give a full proof. $\endgroup$ – Michael Rozenberg Aug 14 '17 at 16:33
  • $\begingroup$ Before I post my proof are you agree with this fact : the maximum of $ab$ with the two conditions $a^4+b^4+c^4=3$ and $a\geq b \geq c $ is $$\sqrt{\frac{3}{2}}$$ ? $\endgroup$ – user448747 Aug 14 '17 at 20:20

First of all we prove this inequality with $a^4+b^4+c^4=3$:

$$\frac{2}{3-a(b+c)}+\frac{1}{3-2bc}\leq 3$$

If we put this with $a\geq b \geq c$ :




Your inequality is equivalent to this :




Now the idea is to use an identity :


The inequality becomes :


Notice that we have just in the inequality elements of the form $BC$ or $B+C$

So we put :


And now remark that $bc$ have his maximum when $B=\frac{\lambda}{2}$ and $C=\frac{\lambda}{2}$

It's the same thing in the general inequality (we can replace $BC$ by $BC=\frac{\lambda^2}{4}$) so we have this inequality with one variable :


Wich is equivalent to :


Now it's easy to remark that the function have a maximum for $\lambda=2$ wich is $3$

So we have prove the following inequality with some conditions :

$$\frac{2}{3-a(b+c)}+\frac{1}{3-2bc}\leq 3$$

Now the idea is to combine this with the theorem of logarithmic majorization for three variables :

Theorem :

Let $a,b,c,d,e,f$ be positive real number , with $a\geq b \geq c$ , $e\geq d \geq f $ under the three following conditions :

$a\geq d$ , $ab\geq de$ , $abc\geq def$ so we have :

$$a+b+c\geq d+e+f$$

The inequality to prove is :

$$\sum_{cyc}\frac{1}{2-3ab}\leq \frac{2}{3-e(f+d)}+\frac{1}{2-3df}\leq 3 $$

With $a^4+b^4+c^4=e^4+f^4+d^4=3$

And $d=1$,$f=bc$,$e=(2-(bc)^4)^{\frac{1}{4}}$

Now its easy to see that we have :

$\frac{1}{2-3ab}\geq \frac{1}{2-3ac}\geq \frac{1}{2-3bc}$


$\frac{1}{3-e(f+d)}\geq \frac{1}{2-3df}$

But as we have said in a comment the maximum of $ab$ is $\sqrt{1.5}$ and $0\leq bc \leq 1$

And :

$e(f+d)=(2-(bc)^4)^{\frac{1}{4}}(1+bc)\geq \sqrt{1.5}$ for $bc\geq0.5$

So we have :

$\frac{1}{3-e(f+d)}\geq \frac{1}{2-3\sqrt{1.5}}\geq\frac{1}{2-3ab}\geq \frac{1}{2-3ac}$

So you just have to apply the theorem to have :

$$\sum_{cyc}\frac{1}{2-3ab}\leq \frac{2}{3-e(f+d)}+\frac{1}{2-3df}\leq 3 $$

For the case $bc\leq 0.5$ you just have to change the parameters like this :


So we have :

$e(f+d)=(2-\frac{1}{16}-(16bc)^4)^{\frac{1}{4}}(1+bc)\geq \sqrt{1.5}$ for $bc\leq0.5$

And the reasoning is the same.


  • $\begingroup$ Now it would right... :) $\endgroup$ – user448747 Aug 15 '17 at 20:30

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.